Epidemiological study of consanguineous marriage and its effects - Sakre, Mohin M.; Bendigiri, Nazir Ahmed D.; Tenglikar, Sharad G.; Swati, Amruta I. (International Journal Of Community Medicine And Public Health, 2017)
Background: Consanguinity increases the risk of congenital anomalies, autosomal recessive disorders, perinatal and antenatal morbidities. The objective of this study was to know the effects of consanguineous marriages and educate the people regarding the effects of the same. Methods:A community based Cross Sectional study was conducted amongst 130 married couples in the field practice area of KBNIMS, Kalaburgi, Karnataka, India by using simple random sampling technique. Data was collected in pre designed pre tested questionnaire. Results: Out of 130 married couples, 58 were consanguineously marriage (44.6%). Among these families, consanguineous marriages were more in Muslim families (56.05%) as compared to Hindu families (25%). Prevalence of abortions and preterm deliveries was noted to be 60% and 64.28% respectively in consanguineous marriages. It had been witnessed that 66.6% of hearing defects in the community were in consanguineous families and a 100% of all vision defects were seen in consanguineous conceptions. Conclusions:As per the study it was found that the prevalence of consanguinity was more in the Muslim population than in Hindu population. Maternal and child morbidity were more prevalent in consanguineous marriages as compared to non-consanguineous marriages. There is a lack of awareness and knowledge about the ill effects of consanguinity. Health education and genetic screening were suggested to curb consanguineous marriages in order to prevent adverse outcomes for better health.